Eigenvalue problems with unbalanced growth - Chorfi, Nejmeddine; Papageorgiou, Nikolaos S.; Radulescu, Vicentiu (Elsevier, 2025)
We consider a nonlinear eigenvalue problem driven by the nonautonomous (p, q)-Laplacian with unbalanced growth. Using suitable Rayleigh quotients and variational tools, we show that the problem has a continuous spectrum which is an upper half line and we also show a nonexistence result for a lower half line.

We consider a nonlinear eigenvalue problem driven by the nonautonomous (p, q)-Laplacian with unbalanced growth. Using suitable Rayleigh quotients and variational tools, we show that the problem has a continuous spectrum which is an upper half line and we also show a nonexistence result for a lower half line.
Eigenvalue problems with unbalanced growth
Keywords: Unbalanced growth; Eigenvalues; Eigenfunctions; Continuous spectrum; Bounded solution; Unbalanced growth; Eigenvalues; Eigenfunctions; Continuous spectrum; Bounded solution